Heinemann explore science: big book 2 - Johnston, Jane; Herridge, Deborah (Heinemann Oxford, 2004)
The "Heinemann Explore Science: Big Book" is an interactive educational resource designed to engage young learners in the fundamentals of science. It features vibrant illustrations and accessible text that cover a variety of scientific topics, making complex concepts easy to understand for early readers. The big book format is perfect for group discussions and hands-on activities, encouraging exploration and curiosity.